Analisis Harga Pokok Produksi Ice Cream Gellato Pada PT. Patra Kartika Di Samarinda - Danna Solihin, Rendi Saputra, H. Eddy Soegiarto K, (EKONOMIA, 2020)
Problems experienced by PT. Patra Kartika is a company that has never applied the method of calculating the cost of production of gellato ice cream products accurately and accurately in accordance with the calculation of the usual cost of the order. This study aims to compare the calculation of the cost of goods set by the company with the cost of goods calculated based on the cost method of the order.The theoretical basis used is the method of order cost. The analytical tool used is the allocation of costs along with the relative selling value method and the collection of cost of goods manufactured by the cost method of the order.From the results of the analysis, it is known that the company has not accurately and accurately charged production costs, according to the company the cost of Cream Cheese ice cream products is Rp. 1,268,800.00, for Oreo flavor is Rp. 1,149,400.00, for Vanilla flavor is Rp. 1,295,200.00, for Monster Ink taste is Rp. 1,072,160.00, for Ovaltine flavor is Rp. 710,160.00, for Nutella flavor is Rp. 1,074,800.00, for Mocca flavor is Rp. 692,160,00, for Clocolato flavor is Rp. 1,211,800.00, for the taste of Buble Gum is Rp. 782,880.00, for Green Tea flavor is Rp. 773,160.00. While according to the analysis of the cost price of Cream Cheese ice cream products is Rp. 1,296,125.00, for Oreo flavor is Rp. 1,196,625.00, for Vanilla flavor is Rp. 1,318,125.00, for the taste of Monster Ink is Rp. 1,084,500.00, for Ovaltine flavor is Rp. 735,075.00, for Nutella taste is Rp. 1,086,700.00, for Mocca taste is Rp. 720,075.00, for Clocolato flavor is Rp. 1,248,625.00, for flavor Buble Gum is Rp. 795,675.00, for Green Tea flavor is Rp. 787,575.00.After testing the hypothesis by holding a calculation of the cost of production based on the order price method, it can be seen that the calculations made by the company are lower than the calculation using the cost method of the order. So the hypothesis put forward by the author can be accepted.